Leadership Effectiveness of the One-Roof Principal at SDN 10 Kisam Tinggi and One-Roof SMPN Bandar Alam Lama OKU Selatan - Tirta Mulyadi; Dasep Supriatna; Mulyadi Mulyadi; Mokhamad Yaurizqika Hadi; Heri Dermawan (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to find out how effective the leadership of one-roof school principals is at SDN 10 Kisam Tinggi and One-roof SMPN Bandar Alam Lama OKU Selatan, as well as what are the inhibiting factors and supporting factors for the effectiveness of the leadership of one-roof school principals at SDN 10 Kisam Tinggi and One-roof SMPN Bandar Alam Lama OKU Selatan. This research uses descriptive research with a qualitative research approach. In this study, the informants were the principal, vice principal, and teacher. The data collection techniques in this study are observation, interviews, and documentation. At the same time, the method used in data analysis is data reduction—the presentation of data and conclusion. The results of this study indicate that the effectiveness of the leadership of the one-roof school principal at SDN 10 Kisam Tinggi and the one-roof SMPN Bandar Alam Selatan has been running effectively. The point of the principal's leadership is measured by the number of results issued, the level of satisfaction obtained, the creative product, and the intensity to be achieved. As for the inhibiting factors, namely schools that are far from the sub-district, signal difficulties, and a lack of teacher human resources, however, this has begun to be resolved with the strategy carried out by the school principal. The supporting factors are the presence of civil and non-civil servant teachers, as well as adequate facilities and infrastructure for the education process.